2011
DOI: 10.1007/s00394-011-0263-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tart cherry juice (Prunus cerasus) on melatonin levels and enhanced sleep quality

Abstract: These data suggest that consumption of a tart cherry juice concentrate provides an increase in exogenous melatonin that is beneficial in improving sleep duration and quality in healthy men and women and might be of benefit in managing disturbed sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
6
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 25 publications
1
138
6
6
Order By: Relevance
“…The consumption of 8 ounces of tart cherry juice in the morning and nighttime for 2 wk was associated with a significant reduction in insomnia severity and WASO in adults with chronic insomnia (43). Howatson et al (45) later replicated the study in a population of young, healthy adults. One week of tart cherry juice supplementation increased urinary melatonin concentrations, TST, and SE compared with a placebo juice.…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 94%
“…The consumption of 8 ounces of tart cherry juice in the morning and nighttime for 2 wk was associated with a significant reduction in insomnia severity and WASO in adults with chronic insomnia (43). Howatson et al (45) later replicated the study in a population of young, healthy adults. One week of tart cherry juice supplementation increased urinary melatonin concentrations, TST, and SE compared with a placebo juice.…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 94%
“…following exercise [9] and improve sleep quality [10,11]. Despite previous studies in cell culture and animal 40 models, where cherry extracts have been shown to exert a range of cardio-protective effects [12,5], there has…”
mentioning
confidence: 99%
“…16 In fact, cherry concentrate, containing 85 µg of melatonin, increased 6-sulphatoximelatonin levels in urine by 17%. 17 Drinking 400 mL per day of a "stabilized" grape juice also elevated the 6-sulphatoximelatonin concentration in urine. 18 Serum melatonin is rapidly hydroxylated to 6-sulphatoximelatonin in the liver, is excreted by the kidneys, and has a half-life of approximately 30 minutes.…”
Section: Melatonin Content In the Human Bodymentioning
confidence: 97%